Utilizing Natural and Man-made Resources for Economic Development: What Are the Mechanisms and Why? - (:unkn) unknown (My University, 2017)
This dissertation studies the roles of natural resources in determining economic outcomes such as innovation, investment, profitability and economic growth. The first chapter studies the ease of substitution between energy and other production inputs over time and across countries. Improvements in energy efficiency over the past decades have substantially decreased the amount of energy used per unit of capital. Yet, previous literature often assumes a constant elasticity of substitution between capital and energy. In this chapter, we develop a Solow growth model with a variable elasticity of substitution (VES) between production inputs and show that the long-run growth rate directly depends on the behavior of this VES over time. Next, using country-level data from 108 countries between 1971 and 2011, we provide the first empirical evidence for a capital-energy VES. Specifically, the elasticity of substitution between capital and energy positively relates to a country's level of economic development and environmental protection efforts. Our results imply that growth-enhancing policies can ease the substitution between capital and energy, which in turn can foster long-run economic growth. In the second chapter, I study the risk and return behavior of green bonds, a new financial instrument that supports green projects around the world. Since its inception in 2007, the green bond market has experienced a compound growth rate of 50% annually. In 2014, green bond issuance totaled USD 36.6 billion, more than threefold its previous year's level of USD 11 billion. This paper is the first to analyze the volatility behavior of the green bond market using data on daily closing prices of the S&P green bond indices between April 2010 and April 2015. Building on a multivariate GARCH framework, I find that compared to the ``labeled'' segment of the green bond market, the ``unlabeled'' segment experiences smaller volatility clustering. I also found a time-varying spillover effect between the green bond market and the overall conventional bond market. These results are meaningful insights into this new, yet very promising market, therefore, have important implications for asset pricing, portfolio management and risk management. The third chapter evaluates the role of a fossil fuel tax and research subsidy in directing innovation from fossil fuel toward renewable energy technologies in the electricity sector. Using a global firm-level electricity patent database from 1978 to 2011, we find that the impact of fossil fuel taxes on renewable energy innovation varies with the type of fossil fuel. Specifically, a tax on coal reduces innovation in both fossil fuel and renewable energy technologies while a tax on natural gas has no statistically significant impact on renewable energy innovation. The reason is that easily dispatchable energy sources (e.g., coal-fired power) need to complement renewable energy technologies (e.g., wind or solar) in the grid because renewables generate electricity intermittently. Our results suggest that a tax on natural gas, combined with research subsidies for renewable energy, may effectively shift innovation in the electricity sector towards renewable energy. In contrast, coal taxation or a carbon tax that increases coal prices has unintended negative consequences for renewable energy innovation. Finally, the last chapter of my dissertation takes a closer look at the efficiency of firms in developing countries. The private sector is the primary source of employment and local development in developing countries. Previous research in developing countries has documented a number of factors contributing to firm-level efficiency. However, which of these factors are the most important drivers of efficiency? This paper ranks the relative importance of the firm-level efficiency determinants in a transitional economy, using a comprehensive firm-level panel data set in Vietnam between 2005 and 2013. The empirical results show that firm-specific production and labor characteristics are the most significant determinants of efficiency. In contrast, legal factors such as formalization and government financial support play a modest role, due to the crowding-out effect of corruption. Thus, firms actively seeking to improve their own production process and labor force can be well-rewarded. Moreover, government technical supports and human resource training programs, combined with anti-corruption efforts, are beneficial for firm-level efficiency, thereby improving the living standards in developing economies.